Radiotherapy-Associated Long-term Modification of Expression of the Inflammatory Biomarker Genes ARG1, BCL2L1, and MYC - Manning, Grainne; Tichý, Aleš; Sirák, Igor; Badie, Christophe (Frontiers in Immunology, 2017)
Ionizing radiation (IR) exposure of cells in vitro and in vivo triggers a complex cellular response amongst which modifications of gene expression have been consistently reported. Nevertheless, little is currently known about the transcriptionally responsive genes which play a role in the inflammation response. In order to improve our understanding of such transcriptional response to radiation in vivo, we simultaneously monitored the expression of 249 genes associated with the inflammation response over the course of the radiotherapy treatment in blood of patients treated for endometrial or head and neck cancer. We have identified genes whose transcriptional expression is either up-regulated (ARG1, BCL2L1) or down-regulated (MYC) several fold in vivo. These modifications were consistently detected across patients and further confirmed by Quantitative Real-Time Polymerase Chain Reaction (QRT-PCR); they were specifically significant towards the end of the radiotherapy treatment, five weeks following the first radiation fraction and more pronounced in endometrial patients (respectively 2.9, 4.1 and 1.8 times). Importantly, in an attempt to correlate expression levels with normal tissue reaction to IR, we also identified three other genes CD40, OAS2 and CXCR1 whose expression level fluctuations during radiotherapy were more pronounced in patients developing late normal tissue responses to curative radiotherapy after the end of the radiotherapy treatment. Overall, we identified inflammation-associated genes which are promising biomarkers of ionizing radiation exposure and susceptibility to radiation-induced toxicity.